The Influence of Corporate Governance and Intellectual Capital towards Financial Distress (Empirical Study of Manufacturing Company in IDX for the Period of 2014-2016) - Muhammad Rasil Fashhan; Vita Elisa Fitriana (President University Press, 2018)
This study aims to test and find empirical evidence on the effects of corporate governance and intellectual capital on financial distress. In this study, the data sample used are manufacturing companies that publish their financial reporting in rupiah currency and listed in Indonesia Stock Exchange. Data collection method using purposive sampling and collected 249 samples from 2014-2016. The method of analysis used in this study is multiple regression analysis. The results of this study indicate that corporate governance does not have a significant effect on the financial distress of the company. While the relationship between intellectual capital and financial distress of the company showed a significant positive effect.